Research on Plastic Zone Evolution Law of Surrounding Rock of Gob-Side Entry Retaining under Typical Roof Conditions in Deep Mine - Jingke Wu; Yun Dong; Yang Jiang; Yushun Yang; Huasheng Sun; Deyu Yin; Wenhu Gu (Shock and Vibration)
To solve the control problem of the surrounding rock of gob-side entry retaining under typical roof conditions in deep mines, we conduct theoretical analysis, numerical simulation, and actual measurements. Starting from the plastic zone of the surrounding rock, the serious damage area, the degree and scope of damage, and the dynamic evolution process of the surrounding rock of the gob-side entry retaining are systematically analyzed under four typical roof conditions in deep mines; the expansion and evolution laws of the plastic zone of the surrounding rock are expounded; and a key control technology is proposed. The results indicate that (1) the plastic failure of surrounding rock was concentrated mainly on the coal side and on the floor, especially in the filling body. The plastic zone of the surrounding rock of the gob-side entry retaining with the thick immediate roof was widely distributed and deep, but the plastic failure of the filling body was not obvious. The plastic failure of the surrounding rock of the gob-side entry retaining with the compound roof was mainly concentrated on the roof, filling body, and floor of the filling area. (2) According to the typical roof conditions of the deep gob-side entry retaining, the order of the degree of damage to the surrounding rock was as follows: thick immediate roof, compound roof, thin immediate roof, and thick-hard roof. (3) A “multisupport structure” control system is proposed for the gob-side entry retaining in a deep mine, including measures for enhancing the bearing performance of the anchorage system, increasing the strength of the cataclastic coal-rock mass, enhancing the bearing capacity of the filling body, and increasing the bearing capacity on the tunnel side. The proposed technology was applied to the deep gob-side entry retaining project in the east area of Panyi Mine, and it effectively fulfilled the reuse requirements of gob-side entry retaining in deep mines.